Analisis Perbedaan Penggunaan Metode Anuitas dan Proporsional Murabahah pada Bank Syariah - Alya Sugiarti; Tengku Syafira Varizka Fery; Yasmin Aulia; Dedek Kustiawati (Publikasi Indonesia, 2022)
This study aims to analyze the differences in the use of proportional annuity and murabaha methods in Islamic banks. This study uses a qualitative approach by describing and describe the data through the opinions of several experts, experiences, and theories related to differences in the use of annuity and proportional murabaha methods in Islamic banks. Based on the method used, it is concluded that the annuity method and the proportional method are methods that are commonly applied in Islamic financial institutions and provide benefits (mashlahah) for the growth of Islamic banks. The purpose of using the annuity and proportional method is to implement Islamic bank financial reporting in a good, accurate, measurable, and in accordance with sharia principles through sharia accounting. The difference between the annuity method and the proportional method lies in the income and expenditure of murabaha financing, the difference between the effective value and the value of the murabaha contract/contract is amortized over the term of the contract using a variety of different methods, and margin income on murabaha contracts.